Full Robotic Distal Pancreatectomy: Safety and Feasibility Analysis of a Multicenter Cohort of 236 Patients. (February 2020) - Alfieri, Sergio; Boggi, Ugo; Butturini, Giovanni; Pietrabissa, Andrea; Morelli, Luca; Di Sebastiano, Pierluigi; Vistoli, Fabio; Damoli, Isacco; Peri, Andrea; Lapergola, Alfonso; Fiorillo, Claudio; Panaccio, Paolo; et al.
Introduction . Despite the widespread use of the robotic technology, only a few studies with small sample sizes report its application to pancreatic diseases treatment. Our aim is to present the results of a multicenter study on the safety and feasibility of robot-assisted distal pancreatectomy (RDP). Materials and Methods . All RDPs for benign, borderline, and malignant diseases performed in 5 referral centers from 2008 to 2016 were included. Perioperative outcomes were evaluated. Results . Two hundred thirty-six patients were included. Spleen preservation was performed in 114 cases (48.3%). Operative time was 277.8 ± 93.6 minutes. Progressive improvement in operative time was observed over the study period. Conversion rate was 6.3%. Morbidity occurred in 102 cases (43.2%), mainly due to grade A fistulas. Reoperation was required in 10 patients. Postoperatively, 2 patients died of sepsis due to a grade C fistula. Hospital readmission was necessary in 11 cases. A R0 resection was always achieved, with a mean number of 16.2 ± 15 harvested lymph nodes. Conclusion . To our knowledge, this is one of the largest RDP series. Safety and feasibility including the low conversion rate, the high spleen preservation rate, the adequate operative time, and the acceptable morbidity and mortality rates confirm the validity of this technique. Appropriate oncological outcomes have been also obtained.